Should Immigrants Culturally Assimilate or Preserve Their Own Culture? Individual Beliefs and the Longevity of National Identity - Peter Grajzl; Jonathan Eastwood; Valentina Dimitrova-Grajzl (Center for Economic Studies and ifo Institute (CESifo), 2017)
We develop and empirically test a theory concerning individual beliefs about whether immigrants should culturally assimilate into the host society or preserve their own cultural norms. We argue that when national identity is a source of intrinsic utility, the longevity of national identity influences a national identity's perceived resilience to an ostensible immigrant threat and, thus, affects individuals' beliefs about the need for immigrants' cultural assimilation. Empirical evidence based on data from countries of wider Europe supports our theory. An expert survey-based measure of the longevity of national identity, first, exhibits a robustly negative effect on the strength of individual preferences in favor of immigrants' cultural assimilation and, second, is an important contextual moderating variable that shapes the effect of individual-level characteristics on their beliefs. Thus, individual beliefs about the necessity of immigrants' cultural assimilation versus accommodation of cultural diversity reflect a historically-rooted sense of national identity.
Keywords: Z13; J18; D72; P51; 330; cultural assimilation; immigrants; individual beliefs; national identity; longevity